2016
DOI: 10.1073/pnas.1603738113
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 contributes to exhaustion of T lymphocytes during chronic viral infection

Abstract: The protein encoded by the autoimmune-associated protein tyrosine phosphatase nonreceptor type 22 gene, PTPN22, has wide-ranging effects in immune cells including suppression of T-cell receptor signaling and promoting efficient production of type I interferons (IFN-I) by myeloid cells. Here we show that mice deficient in PTPN22 resist chronic viral infection with lymphocytic choriomeningitis virus clone 13 (LCMV cl13). The numbers and function of viral-specific CD4 T lymphocytes is greatly enhanced, whereas ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Similar to ours, Maine et al found that PTPN22-deficient mice show accelerated viral clearance of LCMV Cl13 infection by producing higher numbers of viral-specific CD4 and CD8 T lymphocytes with heightened function (30). PTPN22 deficiency did not result in a change in the number of GP 33–41 -specific LCMV-specific CTLs 8 dpi.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to ours, Maine et al found that PTPN22-deficient mice show accelerated viral clearance of LCMV Cl13 infection by producing higher numbers of viral-specific CD4 and CD8 T lymphocytes with heightened function (30). PTPN22 deficiency did not result in a change in the number of GP 33–41 -specific LCMV-specific CTLs 8 dpi.…”
Section: Discussionsupporting
confidence: 82%
“…PTPN22 function in additional cell types likely has an important effect on T‐cell‐driven inflammation. For example, in myeloid cells, rather than act as a negative regulator, PTPN22 enhances production of type 1 interferons (IFNs) . Conversely, PTPN22 negatively regulates type 1 IFN‐receptor signalling pathways .…”
Section: Non‐cell Intrinsic Effects Of Ptpn22 On T‐cellsmentioning
confidence: 99%
“…A clear example of cell‐extrinsic effects of PTPN22 on T‐cell function comes from studies of chronic viral infection. In this regard, several studies reported that PTPN22‐deficient mice were more efficient at clearing chronic lymphocytic choriomeningitis virus (LCMV) infection . Ptpn22 −/− mice infected with the persistent LCMV clone 13 had increased numbers and function of virus‐specific CD4 + T‐cells and CD8 + T‐cells .…”
Section: Non‐cell Intrinsic Effects Of Ptpn22 On T‐cellsmentioning
confidence: 99%
See 2 more Smart Citations